DIETARY COMPLIANCE OF ELDERLY WITH GOUT IS INCREASING WITH THE KNOWLEDGE INCREASEMENT - Wahyu Nur Pratiwi; Ely Isnaeni; Paramita R. Gayatri; Wahyu Sri Astutik; Yuan G. Pratama (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Gout is a disease that is experienced by many elderly people. Gout treatment management can be successful with the sufferer's compliance, especially diet compliance. To be able to adhere with the diet that must be followed, elderly people need to have good knowledge about their disease. More than half of the elderly in Kauman Village, Tulungagung who were found during the initial data collection had limited melinjo-based foods but had not limited other foods that increase uric acid levels even though most had received education about gout. This study determine wheter there are relationship between knowledge about gout and dietary compliance in elder people with gout in Kauman, Tulungagung or not. This study was cross sectional research with 187 respondents. Spearmen rank correlation test result showed a significance value (0.000) with 0.728 of coefficient value. Knowledge about gout showed positive and strong relationship with dietary compliance in elderly people with gout. It can be inferred that the better knowledge, the better and higher respondents dietary compliance